The Maneuver Capability of Malaysian Chinese Business During the Era of New Economic Policy - Sidek, Abdul Halim (International Journal of Engineering and Technology, 2018)
The Chinese business in Malaysia during the era of the NEP (New Economic Policy) was able to translate their business momentum into a consistent and competitive performance thereby making it possible to continue to lead the domestic business environment despite the many challenges posed by the NEP. This study employed the Structure, Conduct and Performance (SCP) model approach in assessing the performance of the Chinese business especially in the transformation of business structure, strategy, innovation and achievement. This study is a historical study conducted through primary source-based business documents and archival sources. As a result, the study discovered that the business strategy used, particularly the maneuver capability factors in Chinese-owned companies. Business diversification methods were common strategies applied by the Chinese enterprises to increase the number of firm size during the period of the implementation of NEP era. The companies responded to the government’s call in opening up the ownership of shares for the Malay-Bumiputera investors without affecting their performance. Innovation to the preservation of Chinese-owned businesses in the era of NEP indicates that the companies practiced merger and acquisition as well as in strengthening research and development in the company. Overall, the SCP model used has proved that the dynamics of the company's business in the Chinese business based on the concept of maneuver allowed Chinese owned companies not only to survive, but to compete successfully and expand tremendously during the NEP era.